Car driving in schizophrenia: can visual memory and organization make a difference?. (25th January 2013) - Lipskaya-Velikovsky, Lena; Kotler, Moshe; Weiss, Penina; Kaspi, Maya; Gamzo, Shimrit; Ratzon, Navah
Abstract: Purpose : Driving is a meaningful occupation which is ascribed to functional independence in schizophrenia. Although it is estimated that individuals with schizophrenia have two times more traffic accidents, little research has been done in this field. Present research explores differences in mental status, visual working memory and visual organization between drivers and non-drivers with schizophrenia in comparison to healthy drivers. Methods : There were three groups in the study: 20 drivers with schizophrenia, 20 non-driving individuals with schizophrenia and 20 drivers without schizophrenia (DWS). Visual perception was measured with Rey-Osterrieth Complex Figure test and a general cognitive status with Mini-Mental State Examination. Results : The general cognitive status predicted actual driving situation in people with schizophrenia. No statistically significant differences were found between driving and non-driving persons with schizophrenia on any of the visual parameters tested, although these abilities were significantly lower than those of DWS. Conclusion : The research demonstrates that impairment of visual abilities does not prevent people with schizophrenia from driving and emphasizes the importance of general cognitive status for complex and multidimensional everyday tasks. The findings support the need for further investigation in the field of car driving for this population – a move that will considerably contribute to the participation and well-being. Implication for Rehabilitation: Unique approach for driving evaluation in schizophrenia should be designed since direct applications of knowledge and practice acquired from other populations are not reliable. This research demonstrates that visual perception deficits in schizophrenia do not prevent clients from driving, and general cognitive status appeared to be a valid determinant for actual driving. We recommended usage of a general test of cognition such as Mini-Mental State Examination, or conjunction number of cognitive factors such as executive functions (e.g. Trail Making Test) and attention (e.g. Continuous Performance Test) in addition to spatial-visual ability tests (e.g. Rey-Osterrieth Complex Figure test) for considering driving status in schizophrenia.